THE NEUROSIS OF RACISM: PSYCHOANALYTIC INTERFACES BY LÉLIA GONZALEZ - Jonas Ribeiro, Magno (Revista Gênero e Interdisciplinaridade, 2024)
This paper aims to present an analysis of racism based on the studies of Brazilian philosopher and sociologist Lélia González. The author brought a different view from her contemporaries on this subject, since racism had its premises of analysis only through sociology. With this, Lélia González brought richness and an innovative reflection on how we can broaden and deepen the reflection on this concept, expanding and making intersections with the psychoanalysis of Sigmund Freud and Jacques Lacan, in order to raise the following question within several questions: does racism as we know it until its extension to structural racism have in its genesis an influence of the psychoanalytic unconscious?Finally, the work intends to lead the reader to reflections on the new perspectives that Lélia González inserted into the studies of racism so that we can understand what this concept would be and how it operates in the unconscious of the Brazilian individual based on a neurosis; a concept studied in psychoanalysis.